Evaluation of performance of key hits using input data, electromyography, and video analysis - Miyono Okinaka; Tsunehiko Wada (Japanese Society of Physical Fitness and Sports Medicine, 2023)
Esports players often use the fingers on their left hand to produce quick key hits on keyboards. It is unknown whether such hits can be a burden on fingers or cause overuse injuries. Numerous studies have focused on key hits; however, those studies have primarily focused on speed. Therefore, in this study, we evaluate rapid key hits using a combination of input data, video data, and surface electromyography (EMG) for fingers that are not accustomed to moving rapidly. Ten male subjects were asked to repeatedly hit the same key on a keyboard quickly using their left ring finger for 30 s. The results indicated that the input speed of a continuous single hit (6.48 Hz for 0-5 s) decreased over time (5.02 Hz for 25-30 s). Matching input and surface EMG data revealed movement with muscle activity, but without an input, that is, a miss-hit. Video results demonstrated that some subjects hit in a flexible manner, while others hit with unnatural form. Until now, there was only data on whether the speed was fast or slow for rapid key hits. A combined analysis of input data, EMG data, and video data can be used to evaluate miss-hits and hitting form.